Introducing International Business Management Concept to High School Students - Aji Irawan, Damar; Oey, Elia; Hansopaheluwakan, Scherly (SEEIJ (Social Economics and Ecology International Journal), 2023)
This community service aims to introduce the international business management concept to high school students. The program lasted around a month and was divided into 13 sessions in the form of online training. Two steps were taken to conduct the community service. The first step was to develop the training content and the second step was to deliver the online training program. 553 high school students in 2021 and 188 high school students in 2022 were selected to attend the program. However, in 2021 only 59 and in 2022 only 4 high school students participated in all sessions. The decreasing rate of attendance is alarming even though after finishing the online training sessions, the participants gained new knowledge related to the international business management concept. Hence, this paper aims to evaluate the community service program.